Development of effective microorganisms mudball material for wastewater treatment and mosquito's larvae control - Zarina Zawawi (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
In this work, a little modification of original EM mudball was made by the addition of Malaysia's herbs extracts as the finding that this plants contains derivative compounds, stated as phytochemicals which have a potential to killed mosquito's larvae by acts as poisoning food to them.